Effect of bleaching on the microhardness of tooth-colored restorative materials - Abdolrahim Davari; Maryam Kashfi; Ebrahim Ataei; Danesh Kazemi Alireza (Tehran University of Medical Sciences, 2013)
Background and Aims: Bleaching agents not only affect the tooth structure, but also may alter the properties of restorative materials. The aim of this in vitro study was to evaluate the effect of different bleaching regimens on the microhardness of four tooth-colored restorative materials.   Materials and Methods: Eighty specimens of four restorative materials (Microhybrid resin composite (Z250 (3M, ESPE), nanohybrid composite Z350 (3M, ESPE), packable composite P60 (3M, ESPE), and resin modified glass ionomer Vitremer (3M, ESPE)) were fabricated and were polished after 24 h with Soflex discs (3M,ESPE). Then the specimens were divided into two groups: In office bleach group, 40 specimens (10 of each restorative material) were bleached with hydrogen peroxide 37.5% for 30 min in two sessions with 7 days interval. In home bleaching group, 40 specimens were bleached with carbamid peroxide 22%, 6 h a day for 14 days. Vickers microhardness test were done before and after bleaching (baseline). Finally data were evaluated using analysis of Variance.   Results: Two bleaching regimens were significantly decreased the microhardness values. In Z250 resin composite, the microhardness values before and after bleaching were 95.30 and 92.67 kg/mm2, respectively. for office bleaching (P=0.011) and 95.38 and 92.39 kg/mm2 for home bleaching (P<0.001). In Z350 resin composite, the microhardness values before and after bleaching were 98.29 and 92.41 kg/mm2, for office bleaching (P<0.001) and 97.35 and 93.44 kg/mm2 for home bleaching (P<0.001) respectively. In P60 resin composite, the microhardness values before and after bleaching were 103.10 and 96.16 kg/mm2, respectively. for office bleaching (P=0.045) and 102.61 and 98.16 kg/mm2 for home bleaching (P=0.001). In resin modified glass ionomer (Vitremer), the microhardness values before and after bleaching were 56.79 and 49.41 kg/mm2, respectively. for office bleaching (P=0.004) and 54.17 and 46.50 kg/mm2 for home bleaching (P<0.001). There was no significant difference between two bleaching agents (P=0.365).   Conclusion: Dental bleaching agents decrease the microhardness of tooth-colored restorative materials.